Peran Politik Tokoh Agama pada Pemilu - Muhammad Amin; Izomiddin Izomiddin; Siti Anisya (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
ABSTRACT Studies on religious figures and their role in politics are always interesting to discuss. Because religious leaders themselves have charismatic and religious knowledge that is very attached to them, so that people always talk about religious issues and also other issues including politics. And also using or exploiting religious leaders to win elections is fine, as long as the religious leaders themselves can position themselves as guides in a more positive and better direction. Also, more importantly, the role of religious leaders or kyai in the political arena is not forgetting the noble goal of inviting the public to consciously exercise their right to vote, which of course is to elect a trustworthy leader. The purpose of this research is to find out the role of religious leaders in the 2019 elections. The method used in this research is qualitative research. The role played by religious leaders in winning elections is certainly inseparable from the charismatic authority they have and through the roles and facilities of the role. There are 3 roles played by religious leaders in their roles. First, they act as opinion formers in society. Second, acting as a motivator for the masses, and third, acting as a campaigner. Keywords: religious leaders, elections, politics.